A case report of attending to one critically ill patient with COVID-19 - Ya-Rong Chen; Gui-Ling Zhao; Pei-Fen Ma; Fu-Rong Liu; Xin-Man Dou (Wolters Kluwer Medknow Publications, 2020)
The outbreak of COVID-19 in Wuhan began to spread rapidly in December 2019. It is highly infectious and widely spread. This article summarizes the care experience of one critically ill COVID-19 patient, including the strict implementation of protective measures, avoiding infection, precautions for high-risk caring of tracheal intubation, giving psychological care, improving the coordination, the importance of vital signs, food intake and excretion, and how to reduce the risk of infection during sample collection, as well as strengthening discharge guidance.